The Location of a Tomb of the Pharaoh in Pyramid of Cheops (London Journal of Research In Humanities and Social Sciences, 2024)
The subject of this research is the pyramid of Cheops. The goal is to determine the location of the burial place of the pharaoh and his sarcophagus. To achieve this goal, the following methods were used: Theoretical analysis of scientific and research literature on this problem. Summarizing and systematizing practical data. Processing, synthesis, analysis of the data obtained, building hypotheses and deriving the final result. Graphic accompaniment of the version from later prototypes to the author's description of the purpose of the artifact. The generally accepted version is that the room in the pyramid of Cheops, discovered by the Arabs, is nothing more than the King's Chamber with his sarcophagus. Since then, researchers have been debating whether the upper chamber discovered by Al-Ma'mun is really the King's Chamber, and the object inside it is the sarcophagus of the pharaoh. The author, summarizing numerous works of Egyptologists, conducts his own research. On its basis, he proves that in the so-called Chamber of the Tsar it is not the sarcophagus, but its defective blank.
Keywords: satisfaction with learning; english for effective communication course; and course content